The Hermeneutical Dimension of Quraish Shihab's Interpretation of the Aurat Verses in the Qur'an - Fauzi, Duea Amalia; Asysyifa, Ainuki Astna; Mundzir, Muhammad (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2023)
Quraish Shihab's interpretation of the verses about women's aurat (genitalia) raises much contra among scholars. Quraish Shihab said that there is no limit to women's genitalia because no unequivocal argument mentions it. Therefore, the author explores the factors influencing Quraish Shihab to give rise to such an interpretation. The author uses qualitative research methods, with H. George Gadamer's hermeneutic analysis that aims to reveal an interpretation's theoretical and historical factors. I conclude that there are hermeneutical dimensions in the interpretation of Quraish Shihab, including affective history, namely, the interpretation is influenced by two figures from the socio-historical context when writing. There is a pre-understanding dimension that the aurat is still being debated. The dimension of fusion of horizon, namely the reality of Quraish Shihab when interpreting the Qur'an, pays attention to the reality when the verse comes down and also pays attention to the context when writing. Finally, there is the application dimension, where the interpretation of the aurataffects the understanding of the family and the surrounding community. Dimensi Hermeneutis Penafsiran Quraish Shihab pada ayat-ayat Aurat dalam al-Qur’an.Penafsiran Quraish Shihab terhadap ayat-ayat tentang aurat perempuan menimbulkan banyak kontra di kalangan ulama. Quraish Shihab mengatakan tidak ada batasan aurat perempuan, karena tidak ada dalil jelas dan tegas yang menyebutkannya. Oleh karena itu, penulis menelusuri faktor-faktor yang memengaruhi Quraish Shihab sampai memunculkan penafsiran yang seperti itu. Penulis menggunakan metode penelitian kualitatif, dengan analisis hermeneutika H. George Gadamer yang bertujuan untuk mengungkap faktor teoritis dan historis dari sebuah penafsiran. Penulis menyimpulkan bahwa terdapat dimensi hermeneutis dalam penafsiran Quraish Shihab, antara lain: affective history yakni penafsirannya dipengaruhi dua tokoh dari konteks sosio-hitoris Ketika menulis. Terdapat dimensi pre-understanding, bahwa aurat itu masih diperdebatkan. Adapun dimensi fusion of horison yakni realitas Quraish Shihab ketika menafsirkan Al-Qur’an memperhatikan realitas ketika ayat turun dan juga memperhatikan konteks Ketika menulis. Yang terakhir tedapat dimensi application, di mana penafsirannya tentang aurat mempengaruhi pemahaman keluarga dan masyarakat sekitar.